2020
DOI: 10.3389/fneur.2020.580030
|View full text |Cite
|
Sign up to set email alerts
|

Insights Into the Proteomic Profiling of Extracellular Vesicles for the Identification of Early Biomarkers of Neurodegeneration

Abstract: Extracellular vesicles (EVs) are involved in the development and progression of neurodegenerative diseases, including Alzheimer's and Parkinson's disease. Moreover, EVs have the capacity to modify the physiology of neuronal circuits by transferring proteins, RNA, lipids, and metabolites. The proteomic characterization of EVs (exosomes and microvesicles) from preclinical models and patient samples has the potential to reveal new proteins and molecular networks that affect the normal physiology prior to the appe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 156 publications
0
33
0
Order By: Relevance
“…Application of omics techniques enabled to map the molecular composition of EV in NDs. While EV protein and miRNA alterations have been studied in more frequent Alzheimer’s and Parkinson’s diseases [ 25 , 134 ], only little is known in HD.…”
Section: Exosomes In Huntington’s Diseasementioning
confidence: 99%
“…Application of omics techniques enabled to map the molecular composition of EV in NDs. While EV protein and miRNA alterations have been studied in more frequent Alzheimer’s and Parkinson’s diseases [ 25 , 134 ], only little is known in HD.…”
Section: Exosomes In Huntington’s Diseasementioning
confidence: 99%
“…EVs are capable of encapsulating various macromolecular cargoes such as proteins, nucleic acids and lipids [ 11 , 12 ]; in addition, various receptors and markers may be present on their surface. Although early works described them as cells’ by-products [ 13 ], a lot of studies report the significant role of EVs as biomarkers for a variety of human pathological conditions nowadays [ 14 , 15 , 16 , 17 , 18 ]. The major advantages of EVs as therapeutic carriers encompass: (i) natural biocompatibility as their envelope is formed from the same cell membrane [ 19 , 20 ], (ii) the ability to pass through the blood–brain barrier [ 21 , 22 ] and (iii) their versatility as a therapeutic tool since surface receptors could be easily modified [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additional studies found an increased release of EVs containing α-syn when intracellular protein trafficking through lysosomes was blocked, confirming that lysosomal dysfunction is likely one of the major factors accelerating PD pathology [ 41 - 43 ]. Inhibition of glucocerebrosidase 1 (GBA-1) activity has also increased the release of brain EVs containing α-syn oligomers [ 44 ]. Furthermore, vesicular α-syn is more prone to aggregation than cytosolic α-syn, indicating disease spread in a prion-like fashion from cell to cell.…”
Section: Role Of Evs In the Pathogenesis Of Pdmentioning
confidence: 99%